2022
DOI: 10.1007/s00415-022-11008-y
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive disorders in childhood epilepsy: a comparative longitudinal study using administrative healthcare data

Abstract: Objective The study aimed to assess the risk of cognitive impairment in patients with epilepsy, the impact of age of epilepsy onset on cognition and the temporal relationship of epilepsy onset and intellectual impairment. Methods This longitudinal study analyzed birth cohorts and followed-up children born 2005–2007 up to the age of ten using administrative healthcare data of about 8.9 million members insured by the statutory health insurance “BARMER” in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
0
4
0
2
Order By: Relevance
“…Developmental delay, cognitive deficits, and psychosocial comorbidities represent major challenges for children with epilepsy, resulting in a substantial impairment of quality of life (QoL) besides seizure activity [ 1 ]. Cognitive impairment in children with epilepsy occurs in up to 17% of cases compared to 1.7% in the general population and may rise to 70% in children with intractable epilepsy [ 2 , 3 ]. A worse cognitive status is also strongly associated with lower psychosocial outcomes in adulthood [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Developmental delay, cognitive deficits, and psychosocial comorbidities represent major challenges for children with epilepsy, resulting in a substantial impairment of quality of life (QoL) besides seizure activity [ 1 ]. Cognitive impairment in children with epilepsy occurs in up to 17% of cases compared to 1.7% in the general population and may rise to 70% in children with intractable epilepsy [ 2 , 3 ]. A worse cognitive status is also strongly associated with lower psychosocial outcomes in adulthood [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that epilepsy increases the risk of cognitive disorder in children [ 23 ]. Similarly, in the present investigation, PTZ kindling led to a decline in cognitive function, as evidenced by impaired performance on the MWM test.…”
Section: Discussionmentioning
confidence: 99%
“…Die Angaben zur Inzidenz von Epilepsien im Kindes- und Jugendalter variieren zwischen 41 und 191 Fällen pro 100 000 Kinder 9 , 10 . Die Prävalenz von kognitiven Einschränkungen bei Kindern und Jugendlichen wird mit bis zu 25 % angegeben und variiert in Abhängigkeit von der Altersstruktur der untersuchten Kohorten sowie der Art und des Zeitpunkts der Testung 11 .…”
Section: Epidemiologieunclassified
“…Dabei deuten die Ergebnisse auch darauf hin, dass das Risiko für kognitive Einschränkung größer war, je früher sich die Epilepsie manifestierte ( Abb. 1 ) 10 .…”
Section: Epidemiologieunclassified